2020
DOI: 10.3389/fpsyg.2020.00732
|View full text |Cite
|
Sign up to set email alerts
|

Varying Cognitive Scars – Differential Associations Between Types of Childhood Maltreatment and Facial Emotion Processing

Abstract: Background: Distorted cognitive processing has been found among survivors of child maltreatment. However, different types of abuse and neglect may bring about differences in emotion and attention processing. The present study aimed to detect differential associations between various types of childhood maltreatment and attentional biases in facial emotion processing. Methods: A non-clinical sample was recruited on University campus and consisted of 67 individuals with varying degrees of maltreatment. In an eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 83 publications
10
30
2
Order By: Relevance
“…Experiences of physical abuse were shown to be associated with slower detection of negatively associated faces compared to neutrally associated faces. Past experiences of sexual abuse, however, did not have an impact on individuals' performance in this study (Iffland and Neuner, 2020). In addition, processing of emotional cues varied between types of maltreatment in a facial emotion recognition task (Pollak et al, 2000).…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Experiences of physical abuse were shown to be associated with slower detection of negatively associated faces compared to neutrally associated faces. Past experiences of sexual abuse, however, did not have an impact on individuals' performance in this study (Iffland and Neuner, 2020). In addition, processing of emotional cues varied between types of maltreatment in a facial emotion recognition task (Pollak et al, 2000).…”
Section: Introductionmentioning
confidence: 59%
“…Notably, the relationship of childhood maltreatment and sustained attention was not confounded by the severity of symptoms of depression, even though a sample of depressed individuals was examined. Similarly, attentional processes varied as a function of different forms of childhood maltreatment in a study using a visual search paradigm combining a social conditioning paradigm with a face in the crowd recognition task (Iffland and Neuner, 2020). Specifically, emotional forms of maltreatment were particularly associated with an altered sensitivity in detecting faces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recruitment, and maintenance, of youth with TE is a problem across a host of studies ( Hussey et al, 2006 ; Kinard, 2001 . Furthermore, the use of a dichotomous variable for childhood TE may limit the ability to detect differences by type of TE ( Iffland and Neuner, 2020 ). In addition, information on timing and duration of TE was not collected as part of this project, and thus differential associations based on chronicity and severity of TE to emotion regulation outcomes cannot be inferred from this data and continue to be an important target for research.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to threat in childhood is associated with altered processing of emotional stimuli (e.g., generalization of fear to neutral stimuli), and heightened emotional reactivity (i.e., elevated emotional and neural responses to emotional cues) ( Lavi et al, 2019 ; Pine et al, 2005 ; Pollak and Tolley-Schell, 2003 ). These effects are long-lasting; childhood TEs are related to biased attention and increased emotional reactivity toward negatively-valanced emotional stimuli during childhood and adulthood ( Dannlowski et al, 2012 , 2013 ; Iffland and Neuner, 2020 ; McLaughlin et al, 2014 , 2019 ; Pollak, 2008 ; Sheridan and McLaughlin, 2014 ). These alterations may be emotion-specific; some studies have reported increased biased attention toward sad faces ( Romens and Pollak, 2012 ) and others have reported decreased attention to angry/threatening stimuli ( Pine et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%